Comparing Scapular Position and Scapular Dyskinesis in Individuals with and without Rounded Shoulder Posture - Elham Sarabadani Tafreshi; Afsun Nodehi Moghadam; Enayatolah Bakhshi; Mahan Rastgar (Physical Treatments, 2015)
Purpose: Altered kinematics of the scapula or scapular dyskinesis (downward rotation, anterior tilt, and protraction) contribute to impingement syndrome by decreasing the subacromial space. Given the critical role of scapular position and movement in the function of the shoulder, the aim of this study was to compare scapular position and dyskinesis in individuals with and without rounded shoulder posture.